Novus as the Magnum Opus of the Musico-Spiritual Ministrations of Carlos Santana: An Appraisal of his Works - Osai, Jason (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
The music of Santana, arguably, magnificently embodies thevirtuosity and raw creativity of the sixties, seventies and eighties,the “cool” of the nineties and twenties and the oneness andspiritual essence of the human race. It has therefore demonstratedthe resilient capacity for continually reaching and sensitivelytouching successive generations of fans of multicultural extractionwith passionate musical idioms, which are a fusion ofrock, jazz, blues, soul and Latin and, therefore, serving a musicalmenu of multicultural melodic phraseology that is as unique as itis instantly identifiable, globally. From the sixties to the presentand utilizing personnel from variegated cultural and genre setting,Santana's music has become an event of global culture,transcending genre, crossing national boundaries and culturesand creating music that has emerged the soundtrack for the world.The paper subjects the works of Carlos Santana to critical analysis26.1.2010 [01-16]1covering the musical idioms and lyrical idiomatic expressions fromthe perspective of the universalism of his lyricism and opines thatthere is a religio-philosophical stream of thoughts that runsthrough his albums over a timeframe of more than three decades,from Santana I (1969) to Shaman (2002) from which “Novus” istaken. The paper opines that “Novus,” a song that suavelycombines canal love and the eternity of Divine Love, is the magnumopus of Santana's musical ministrations and mission in which he hasconsistently advocated harmony in humanity from the perspectiveof Mayan philosophies and shamanism. Same as his other workswith spiritual essence, “Novus,” transcends religion and touchesthe human spirit irrespective of color or creed, station or location.“Novus,” the paper concludes, is vintage Carlos Santana—themultidimensional spirit; it represents the quintessence of the man;it is his magnum opus and, therefore, valedictory.